Urban green space: stakeholders’ and visitors’ perception in Kuala Lumpur Malaysia - Hj. Baharuddin, Zainul Mukrim (2010)

(untitled)
Planning, development and maintenance of urban green space is among the key elements of sustainable urban development. Acknowledging and participating in the conservation and enhancement of the urban green space can improve the environment and provide huge benefits to city dwellers. The aim of this paper is to investigate the stakeholders’ and visitors’ understanding of their responsibility and responsiveness towards urban green spaces in Kuala Lumpur.